2002
DOI: 10.1021/jf025630u
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of the Cry1F Insecticidal Crystal Protein in Soil

Abstract: The gene for the core Cry1F insecticidal crystal protein (ICP) from Bacillus thuringiensis Berliner (Bt) has been incorporated into the genome of maize plants, Zea mays L. Plants expressing this ICP are protected from attack by various Lepidopteran pests including the European corn borer, Ostrinia nubilalis (Hübner). The stability of the Cry1F ICP in soil was assessed in a laboratory study designed to determine the persistence of the active protein residue in soil over time, using insect bioassay as the analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…It is estimated that plants often contain only 1-5% protein by weight and that protein structures are known to degrade rapidly in a soil environment. [31,32] It seems unlikely that the preservation of plant-derived peptide/protein structures can completely account for the contributions of proteins and peptides in DOM. It is therefore possible that a significant portion of peptide/protein in DOM arises from the cells of dead and living microbes of either aquatic or terrestrial origin.…”
Section: General Characterisationmentioning
confidence: 99%
“…It is estimated that plants often contain only 1-5% protein by weight and that protein structures are known to degrade rapidly in a soil environment. [31,32] It seems unlikely that the preservation of plant-derived peptide/protein structures can completely account for the contributions of proteins and peptides in DOM. It is therefore possible that a significant portion of peptide/protein in DOM arises from the cells of dead and living microbes of either aquatic or terrestrial origin.…”
Section: General Characterisationmentioning
confidence: 99%
“…Additionally, Stotzky and coworkers [6][7][8][9][10] demonstrated that Bt proteins were adsorbed to soil components, especially clays, and were protected from degradation but retained insecticidal activity. Although conflicting results have been found in assessing Bt protein persistence in soil, previous studies gen-erally indicate that the dissipation is biphasic; the concentration of protein rapidly declines and then the remaining portion dissipates at a much slower rate [11][12][13][14]. In a series of microcosm experiments, Palm et al [12] found that 10 to 40% of the protein remained at the end of a 28-d period.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, there would be further degradation of proteins in the manure due to microbial processes. Even though it has been observed that Cry proteins can bind to certain soil particles (e.g., humic acids, clays) resulting in protection from degradation, a number of studies revealed that there is no accumulation of Cry proteins from GM crops in soil (Herman et al, 2001(Herman et al, , 2002Head et al, 2002;Baumgarte and Tebbe, 2005;Hopkins and Gregorich, 2005;Ahmad et al, 2005;Dubelman et al, 2005;Icoz and Stotzky, 2007;Krogh and Griffiths, 2007;Lawhorn et al, 2009).…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%